Decoding molecular mechanism underlying binding of drugs to HIV-1 protease with molecular dynamics simulations and MM-GBSA calculations. Issue 11 (2nd November 2021) - Yu, Y.X.; Liu, W.T.; Li, H.Y.; Wang, W.; Sun, H.B.; Zhang, L.L.; Wu, S.L.
ABSTRACT: HIV-1 protease (PR) is thought to be efficient targets of anti-AIDS drug design. Molecular dynamics (MD) simulations and multiple post-processing analysis technologies were applied to decipher molecular mechanism underlying binding of three drugs Lopinavir (LPV), Nelfinavir (NFV) and Atazanavir (ATV) to the PR. Binding free energies calculated by molecular mechanics generalized Born surface area (MM-GBSA) suggest that compensation between binding enthalpy and entropy plays a vital role in binding of drugs to PR. Dynamics analyses show that binding of LPV, NFV and ATV highly affects structural flexibility, motion modes and dynamics behaviour of the PR, especially for two flaps. Computational alanine scanning and interaction network analysis verify that although three drugs have structural difference, they share similar binding modes to the PR and common interaction clusters with the PR. The current findings also confirm that residues located interaction clusters, such as Asp25/Asp25ʹ, Gly27/Gly27ʹ, Ala28/Ala28ʹ, Asp29, Ile47/Ile47ʹ, Gly49/Gly49ʹ, Ile50/Ile50ʹ, Val82/Val82ʹ and Ile84/Ile84, can be used as efficient targets of clinically available inhibitors towards the PR.